DTEx: A dynamic urban thermal exposure index based on human mobility patterns. (October 2021) - Yin, Yanzhe; Grundstein, Andrew; Mishra, Deepak R.; Ramaswamy, Lakshmish; Hashemi Tonekaboni, Navid; Dowd, John
Highlights: We developed a novel index called the Dynamic Urban Thermal Exposure index (DTEx). DTEx blends high resolution spatiotemporal human movement and heat hazard patterns. DTEx shows that the highest heat exposure does not always occur in the urban center. Changes in human movement during mass events can increase DTEx by 3-4 categories. DTEx may be useful for real-time heat exposure warnings and urban heat mitigation. Abstract: Background: Extreme heat in light of climate change is increasingly threatening the health and comfort of urban residents. Understanding spatio-temporal patterns of heat exposure is a critical factor in directing mitigation measures. Current heat vulnerability indices provide insight into heat sensitivities within given communities but do not account for the dynamic nature of the human movement as people travel for different activities. Here, we present a new D ynamic urban T hermal Ex posure index (DTEx) that captures the varying heat exposure within urban environments. Methods: We developed the DTEx to understand human heat exposure patterns in a mid-sized city. This index incorporates the human movement pattern and the heat hazard pattern obtained via novel and advanced techniques. We generated the human movement pattern from large-scale, anonymized smartphone location data. The heat hazard patterns were extrapolated via machine learning models from air temperature data measured through vehicle-mounted sensors. The exposure index was then developed by combining the two parameters using their standard-deviation-classified indices. Results: Our exposure index varied between 2 and 12, indicating low to high thermal exposures. Several high-temperature spots associated with a large volume of foot traffic are successfully identified through this DTEx. We observed the hottest spots at shopping plazas but not specifically in the urban center. During the selected football gameday, the exposure index surged across most places near the football stadium but was reduced considerably further away. Discussion: The proposed DTEx is novel because it provides dynamic heat monitoring capability to facilitate heat mitigation strategies at vulnerable locations in urban environments. Combining the mobility data and extensive sensor data generates rich details on the most heat-exposed areas due to human congregation. Such information will be critical for risk communication and urban planning for policymakers. DTEx could also help smart route planning in sustainable cities to avoid heat hazards risks.